2017
DOI: 10.1515/nbec-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Plant stress activated by chlorine from disinfectants prepared on the base of sodium hypochlorite

Abstract: In this study, the phytotoxicity of disinfectants prepared on the base of sodium hypochlorite was determined. For our tests two commercial products, Savo and Dom Amor, as well as 10% NaClO solution were used. While Savo contained only NaClO, Dom Amor contained NaClO and earthworm enzymes. Products on the base of NaClO are used in households for cleaning and disinfection of floors, furniture, sanitary and kitchen equipment. Savo may be used for the disinfection of drinking waters as well. Products with NaClO ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In this case, a relatively low percentage of sterile and surviving microbeads was recorded. Chlorine-containing drugs often exhibit phytotoxicity [25]. The maximum effect of sterilization was achieved with the use of hydrogen peroxide in the E96H38W5 variant.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, a relatively low percentage of sterile and surviving microbeads was recorded. Chlorine-containing drugs often exhibit phytotoxicity [25]. The maximum effect of sterilization was achieved with the use of hydrogen peroxide in the E96H38W5 variant.…”
Section: Discussionmentioning
confidence: 99%
“…The intake process influences fluxes and accumulation of the chlorine in the plants and its distribution within the plants. The fluxes across membranes and between tissues limit growth and water translocation in the plants as well as interfere with photosynthesis through inhibition of photosynthetic pigment production (Fargašová, 2017). In addition, it has been shown that a chlorine cover has been formed during hypochlorite disinfection of rice seeds and this artifact could not be eliminated simply by rinsing the seeds, even thoroughly, with sterile distilled water.…”
Section: Discussionmentioning
confidence: 99%